MEWUJUDKAN KOTA LAYAK ANAK BERBASIS KEBUTUHAN DI KOTA KENDARI - Dewi Anggraini; La Ode Muhammad Elwan; M. Najib Husain (Journal Publicuho, 2023)
This research aims to evaluate the city components that support Kendari City's condition as a Child-Friendly City and analyze the factors that hinder and support this status. A qualitative descriptive method with an ethnographic study approach was used to identify city components such as the residential environment, community environment, school environment, play areas, transportation and health services that support the condition of Kendari City as a Child-Friendly City. The research results show that there are several obstacle factors such as infrastructure problems that affect children's access to education and health services. This evaluation provides a holistic picture of Kendari City's efforts to create a conducive environment for children's development and offers a perspective regarding the challenges that need to be overcome to achieve optimal Child-Friendly City status.